EVALUASI PROGRAM PENGELOLAAN PERPUSTAKAAN SEBAGAI SUMBER BELAJAR di MADRASAH ALIYAH LABORATORIUM KOTA JAMBI MENGGUNAKAN MODEL CIPP - Aris Munandar; Fellina Dwi Kusuminingrum; Muhammad Ferdiansyah; Syahwa Sofia; Ingka Maryani; Zahra Ameilia Putri; Atika Nopriyani; Yeye Muhammad Arif (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to evaluate the effectiveness of library management as a learning resource at Madrasah Aliyah Laboratorium in Jambi City, considering the crucial role of libraries that are still faced with constraints on facilities and resource readiness in the digital era. Using the CIPP (Context, Input, Process, Product) evaluation model with a descriptive qualitative approach, data were collected through in-depth interviews, observations, and questionnaires, then analyzed through the condensation stage until conclusions were drawn. The evaluation results indicate that the program is running quite effectively but has a significant gap in technological vision. In the context aspect, there is full support from the leadership, but the input aspect has major weaknesses due to the lack of digital infrastructure and substandard staff qualifications. In terms of process, circulation services run well although manually and have not been optimally integrated with classroom learning, while the product aspect shows an increase in student reading interest which is still dominated by non-academic fiction collections. It is concluded that the library has not fully functioned as an academic reference center or digital learning, so that thorough strategic planning and technology investment are needed to strengthen the program's effectiveness in the future. ABSTRAK Penelitian ini bertujuan mengevaluasi efektivitas pengelolaan perpustakaan sebagai sumber belajar di Madrasah Aliyah Laboratorium Kota Jambi, mengingat peran krusial perpustakaan yang masih dihadapkan pada kendala fasilitas dan kesiapan sumber daya di era digital. Menggunakan model evaluasi CIPP (Context, Input, Process, Product) dengan pendekatan kualitatif deskriptif, data dikumpulkan melalui wawancara mendalam, observasi, dan kuesioner, lalu dianalisis melalui tahapan kondensasi hingga penarikan kesimpulan. Hasil evaluasi menunjukkan bahwa program berjalan cukup efektif namun memiliki kesenjangan visi teknologi yang signifikan. Pada aspek context, terdapat dukungan penuh pimpinan, namun aspek input memiliki kelemahan utama akibat ketiadaan infrastruktur digital dan kualifikasi staf yang belum standar. Dari sisi process, layanan sirkulasi berjalan baik meski manual dan belum terintegrasi optimal dengan pembelajaran kelas, sementara aspek product menunjukkan peningkatan minat baca siswa yang masih didominasi koleksi fiksi non-akademik. Disimpulkan bahwa perpustakaan belum sepenuhnya berfungsi sebagai pusat rujukan akademik atau pembelajaran digital, sehingga diperlukan perencanaan strategis yang matang dan investasi teknologi untuk memperkuat efektivitas program di masa depan.